2022
DOI: 10.1021/acscatal.2c02773
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Hole Extraction Based on Cascade Band Alignment Boosts Photoelectrochemical Water Oxidation Efficiency

Abstract: Photon energy loss to interfacial charge recombination is one of the key challenges to achieving high efficiencies for solar water splitting in photoelectrochemical cells (PECs). Herein, BiVO4-based photoanodes are constructed, where BiVO4, cadmium sulfide nanosheets (CdS NSs), hole transport molecules (HTs), and oxygen evolution cocatalysts (OECs) assemble sequentially in a cascade band alignment for efficient photogenerated hole extraction and accumulation to OECs. In the photoanode assemblies, CdS NSs act a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…57−60 The suppression of charge recombination was also revealed by the TPV/TPC technique with a slower recombination rate and a longer carrier lifetime on BVO/ TANF (20.9 ms). 61 All these data suggest the effect of TANF in retarding charge recombination on the surface (Scheme 2b).…”
Section: Charge Recombination and Hole Transfer Kineticsmentioning
confidence: 91%
“…57−60 The suppression of charge recombination was also revealed by the TPV/TPC technique with a slower recombination rate and a longer carrier lifetime on BVO/ TANF (20.9 ms). 61 All these data suggest the effect of TANF in retarding charge recombination on the surface (Scheme 2b).…”
Section: Charge Recombination and Hole Transfer Kineticsmentioning
confidence: 91%
“…For example, Hu et al reported a BiVO 4 photoanode with a stacked structure, in which BiVO 4 , cadmium sulde nanosheets, hole transport molecules (carbazole, triphenylamine, and phenothiazine derivatives), and OER catalysts (CoBi) are sequentially assembled by a cascade band alignment for accelerating the hole transfer and water oxidation efficiency. 83 Min et al demonstrated that the formed junction between MnO 2 and the (111) plane of TiO 2 could provide a stronger interface electric eld for boosting the catalytic activity owing to the betting energy levels. 84 Although the above strategies have achieved a favourable effect to some This journal is © The Royal Society of Chemistry 2023 extent, the barrier of charge transfer cannot be completely removed.…”
Section: Selective Interfacial Bondingmentioning
confidence: 99%
“…Small molecular materials that are soluble in water or polar solvents are more suitable for photoelectric catalytic systems. Currently, many research works have reported that organic hole-transporting molecular materials can be used to modify photoanodes as cocatalysts for hole modulation to improve charge separation efficiencies, such as ferrocene ligands, phenothiazine (PTZ) and trifluoroacetic acid [77][78][79][80] . A suitable hole-accepting ligand should satisfy the energy requirement for continuous hole transfer and interact closely with the photoelectrode to enable ultrafast hole transfer.…”
Section: Organic Hole Transfer Materialsmentioning
confidence: 99%
“…A suitable hole-accepting ligand should satisfy the energy requirement for continuous hole transfer and interact closely with the photoelectrode to enable ultrafast hole transfer. Niu et al systematically studied the role of carbazole-derived hole transport molecules anchoring on the surface of a CdS QD/TiO 2 film [80] . As shown in Figure 7, dithiol-functionalized carbazole and a ruthenium coordination compound (RubdaS) were used as a hole transfer molecule and OER catalyst, respectively.…”
Section: Organic Hole Transfer Materialsmentioning
confidence: 99%